A New Strategy to Prepare Poly(2‐methyl‐2‐oxazoline)‐Based Antifouling Coatings: Using UV‐Crosslinked Copolymer Anchors. Issue 4 (23rd January 2019) - Zhu, Haikun; Chen, Lijuan; Zhang, Chong; Atif, Muhammad; Gong, Kai; Chen, Chaoshi; Wang, Yanmei
Abstract: A series of the copolymer, poly(styrene‐random‐glycidyl methacrylate) (P(St‐r‐GMA)), is synthesized by free radical polymerization, and characterized by 1 H NMR spectroscopy and gel permeation chromatography. The various substrates are then modified by P(St‐r‐GMA) under ultraviolet (UV) irradiation. Subsequently, the poly(2‐methyl‐2‐oxazoline) (PMOXA) based coatings are prepared by anchoring amino‐terminated PMOXA onto the P(St‐r‐GMA) modified surfaces through the reaction between the amino group of PMOXA and epoxy group of P(St‐r‐GMA). The results of ellipsometry, X‐ray photoelectron spectroscopy, atomic force microscopy, and water contact angle reveal that PMOXA‐based coatings can be prepared successfully on the substrates through UV‐crosslinked P(St‐r‐GMA) as anchoring coatings. Besides, the PMOXA‐based coatings display not only a superior antifouling property but long‐term stability as well. Furthermore, the location of the coating formed on the substrate can be well controlled through selecting the site of UV irradiation, which can be utilized for the selectivity of protein adsorption (or resistance) on special devices. Abstract : Poly(2‐methyl‐2‐oxazoline) (PMOXA) based coatings are prepared by anchoring amino‐terminated PMOXA onto UV‐crosslinked poly(styrene‐random‐glycidyl methacrylate) modified surfaces. The PMOXA‐based coating displays not only a superior antifouling property but a long‐term stability as well. Furthermore, the location of the coating formed on the substrate can be well controlled through selecting the site of UV irradiation.